The relationship between work-life balance policies and employees’ job satisfaction in government sectors - Lo, Fhung Lin; Dayang Kartini, Abang Ibrahim (-, 2012)
This study aims to identify the relationship between work-life balance policies and employee’s job satisfaction in government sector. The study was conducted in the government sector. Quantitative method was used and five Likert-scale questionnaires were distributed to the respondent. 180 survey questionnaires were distributed to the staff in the government sector in Kuching and 119 were returned and only 114 set of survey questionnaires were useable. The study was conducted to determine the relationship between Work-Life Balance Polices (which is Flexible Working Arrangement, Maternity leave and Childcare policy) and employee’s job satisfaction. The relationship between work-life balance policies and employees’ job satisfaction were estimated using Pearson Correlation Coefficient. The date collected is analyzed using the SPSS version of 17.0. From the analysis, it shows that there is a significant relationship between flexible working arrangement and employee’s job satisfaction (r= 0.602**, p= 0.000) and the relationship between childcare policy and employees’ job satisfaction also shows that there has a significant relationship (r= 0.534**, p= 0.000). The result also shows that the relationship between maternity leave and employee’s job satisfaction, has no significant relationship (r= 0.162, p= 0.082). The contribution of this study and recommendation for human resource practitioners, organization and future researchers also further discussed.